Recycling carbon fibre with an acetone/water solvent and zinc chloride catalyst: resin degradation and fibre characterisation - Keith, Matthew J.; Ingram, Andrew; Leeke, Gary A. (Cranfield University, 2018)
The degradation of a carbon fibre reinforced epoxy resin with an acetone/water mixture and ZnCl2 catalyst was investigated. The solvent/catalyst system achieved a resin removal yield in excess of 94% after 1.5 h at 290°C and 45 min at 300°C. Single fibre tensile testing indicated an increase in fibre strength after the recycling process. The strongest fibres were recovered using a reaction temperature of 290°C and exhibited a strength of 3.21 ± 1.10 GPa. The technique developed therefore appears to recover high quality fibres while reducing the temperature by 30°C and process time by 25% when compared to earlier work.